PENGARUH GOOD CORPORATE GOVERNANCE, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Lu'lu' Luthfiana; Nurma Gupita Dewi (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
The purpose of this study was to determine the effect of good corporate governance represented by the board of directors, board of commissioners and audit committee, capital structure and company size on financial performance. This study used purposive sampling to obtain a sample of 32 banking entities registered on the IDX for the 2019-2021 period. Methods of data collection using the method of documentation. The data analysis technique uses multiple regression analysis using the SPSS version 26 application. The results of this study show that partially the board of directors has a significant positive effect on financial performance while the board of commissioners, audit committee, capital structure and company size have no effect on financial performance